(untitled) (Olhares, 2020)
This article discusses how the form and the content of modern drama – based on Henrik Ibsen’s play "Dollhouse" – can subvert not only the dramatic structure, but also any disciplinary and castrating system. Through a brief journey from Renaissance to Modernity, passing by the birth of Biopower and the Witch hunts, the proposed reflection rediscovers the essence of art: Collective Liberation.